Social Spending in Nepal: A Trend and Impact Analysis - Basyal, Laxman (Economic Journal of Nepal, 2011)
Social programs such as health care and education are generally believed to influence human development and consequently, increased government spending in these programs is expected to result in better social outcomes. The extent to which social indicators response for this depends upon current and past levels of spending as well as the ejj7ciency and equity of spending. The prospects for enhancing the efficiency of spending and improving the equity of spending on social service sectors would be much brighter if spending $441S to increase as health spending strongly affects health indicators and similarly education spending affects education indicators. In this context this paper has attempted to highlight the trend and pattern of government expenditure in the social service sectors and its impact on social indicators in Nepal covering the time period from 1990 to 2004.Key words: Social outcomes; Social services; NepalEconomic Journal of Nepal A Quarterly Publication of the Central Department of Economics, Tribhuvan University, Kirtipur, KathmanduVol. 30, No.4, October-December, Issue No. 120, 2007Page: 260-273Uploaded date: 22 July, 2011